Formulation of Serum Using a Combination of Tamanu Oil and Tea Tree Oil as Antiacne - Ermawati, Dian; Cahyani, Pradina Zustrian; Shahnaz, Ifa; Juniarty, Amelya; Mahardhika, Chandra Leony; Chasanah, Uswatun (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2023)
Acne is a chronic inflammation of the skin caused by bacteria. Tamanu oil contains neoflavonoids and tea tree oil contains terpenes-4-ol, both of which have good antibacterial agents. The combination of Tamanu oil and tea tree oil will produce a preparation synergistic in inhibiting bacterial growth. This study was to determine the best formula for serum preparations with good characteristics and stability against bacteria without irritating the skin. Serum formulation in three different concentrations of Tamanu oil is 0.5%, 0.75%, and 1%, each combined with 2% tea tree oil. Then the characteristics test (organoleptic, homogeneity, viscosity, dispersibility, and pH), stability test (organoleptic, homogenous, and pH) using cyclic temperature stress testing, and antibacterial test against Staphylococcus aureus and Propionibacterium acnes using well-diffusion method and irritation test using Hen’s egg test chorioallantoic membrane (HET-CAM) were carried out. The results showed that the overall viscosity, spreadability, and pH matched the specification, were stable, and had no irritation effect. Serum formulation containing Tamanu oil 1% and tea tree oil 2% is the best antibacterial activity which zones inhibition of 12.5 mm on Propionibacterium acnes and 11.6 mm on Staphylococcus aureus.